O SOFTWARE CABRI 3D COMO FERRAMENTA DE AUXÍLIO AO ENSINO E VISUALIZAÇÃO DE SEÇÕES PLANAS NO CUBO PARA ALUNOS DO ENSINO MÉDIO - Marin, Guilherme Baggio (2013)
This study aimed to investigate the contributions of the software Cabri 3D in the viewing of flat sections in the cube, made by high school students of a private school in Santa Maria, Rio Grande do Sul state. This Research has an investigative methodology, and the data collected is qualitative in nature, so the researcher should analyze and present the results. A group of 29 students of the 3rd year, all from the same class, volunteered for this study. Ten activities were prepared, where students performed sections in the cube using pencil and paper, then these same activities performed using the software Cabri 3D, so we could compare the results. The first three ones consisted in obtaining triangular regions, scalenon, isosceles and equilateral. The following three regions involved four sides to reach regions of six sides, increasing the difficulty of the buildings and the views. In each activity, students recorded, initially, their justifications on paper. Later, in the realization with the use of Cabri 3D, feature of the software itself, was used to type along with the building with the reasoning of the building. This research shows the advantages of using the software in the visualization of plane sections obtained from a cube by planes that intersect its edges. As a product of this master professional dissertation, we designed a Power Point tutorial addressing to the topic of the study proposed.